Perlindungan Hukum Terhadap Intervensi Pemberitaan dalam Kerangka Kemerdekaan Pers Nasional - Fuqoha Fuqoha; Indrianti Azhar Firdausi; Arga Eka Sanjaya (Universitas Serang Raya, 2019)
Law protection for journalists has been guaranteed through legislation as outlined in law number 40 of 1999 concerning the press. Through the press law, the independence of the national press is a priority as a form of protection in the world of the press. In order to safeguard the independence of the national press, an independent body was formed which took care of and supervised the national press, the press council. Among the duties and functions of the press council is to enforce journalistic ethics through a journalistic code of ethics as a guide for journalists both journalists and press companies. The dynamics that occur, violations of the journalistic code of ethics sometimes create clashes with the public or the community who feel disadvantaged which results in conflict with the law. This research is a descriptive qualitative study with a normative juridical approach. From the analysis of this study shows that legal protection against violations of the journalistic code of ethics and the independence of the national press is adjusted to the main laws of the press against the intervention of parties who feel disadvantaged. The independence of the national press is directed at independence and without intervention in a story.